Enfermedad cerebrovascular y sus factores asociados en pacientes diagnosticados en el Hospital General Isidro Ayora de Loja - Benítez Guzmán, Kevin Martín (2021)
Cerebrovascular disease (CVD) has been considered one of the main causes of death worldwide, registering more than 6 million deaths in 2015 according to data from the World Health Organization; Various modifiable factors intervene in its production which, when corrected in time, can prevent this catastrophic pathology. The purpose of the present study was to establish the modifiable and non-modifiable associated factors of cerebrovascular disease; determine the most common type of cerebrovascular disease and the etiology of cerebrovascular disease. A descriptive, retrospective, correlational study with a quantitative approach was carried out; with a population of 103 patients with cerebrovascular disease diagnosed at the Isidro Ayora General Hospital in the period 2017 - 2019. A review of medical records was carried out and the necessary information was collected in data collection sheets, for their subsequent ordering, tabulation and interpretation, as well as statistical analysis through the application of chi square. The results obtained indicated that the majority presented arterial hypertension as the main modifiable risk factor, evident in 62.1% of the cases (n=64), presenting a statistically significant relationship (P=0.000); The non-modifiable factors were female sex with 52.4% (n=54), although there was no statistically significant relationship with CVD (P=0.312), age over 70 years with 54.4% (n=56), mixed ethnicity with 99% (n=102), in addition, it was evidenced that 97% (n=100) did not present any family history of CVD. The most frequent type of CVD was ischemic with 56.3% (n=58); The most frequently determined etiology was intracranial atherosclerosis, with 14.6% (n=15). Key words: stroke, risk factors, hypertension, atherosclerosis.